2015
DOI: 10.1155/2015/986075
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of HO-1 Expression Mitigates Intestinal Ischemia-Reperfusion Injury and Restores Tight Junction Function in a Rat Liver Transplantation Model

Abstract: Aims. This study was aimed at investigating whether elevation of heme oxygenase-1 (HO-1) expression could lead to restoring intestinal tight junction (TJ) function in a rat liver transplantation model. Methods. Intestinal mucosa injury was induced by orthotopic autologous liver transplantation (OALT) on male Sprague-Dawley rats. Hemin (a potent HO-1 activator) and zinc-protoporphyrin (ZnPP, a HO-1 competitive inhibitor), were separately administered in selected groups before OALT. The serum and intestinal muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 48 publications
3
45
0
2
Order By: Relevance
“…HO-1 plays an important role in improving intestinal barrier function. In a rat liver transplantation model, elevation of HO-1 mitigates intestinal ischemia-reperfusion injury and restores TJ function (17), and serum endotoxin, D-Lac and DAO were significantly increased demonstrates this. The presence of bile in the gut is essential for the maintenance of intestinal mucosal barrier function; bile salt deficiency can lead to intestinal mucosal atrophy and intestinal mucosa barrier dysfunction (34).…”
Section: Ho-1 Increased Occludin and Inhibited Phospho-nf-jb P65 Protmentioning
confidence: 91%
See 1 more Smart Citation
“…HO-1 plays an important role in improving intestinal barrier function. In a rat liver transplantation model, elevation of HO-1 mitigates intestinal ischemia-reperfusion injury and restores TJ function (17), and serum endotoxin, D-Lac and DAO were significantly increased demonstrates this. The presence of bile in the gut is essential for the maintenance of intestinal mucosal barrier function; bile salt deficiency can lead to intestinal mucosal atrophy and intestinal mucosa barrier dysfunction (34).…”
Section: Ho-1 Increased Occludin and Inhibited Phospho-nf-jb P65 Protmentioning
confidence: 91%
“…Previous reports have shown that induction of HO-1 expression contributes to protection against liver damage in various liver diseases such as acute liver injury, alcoholic liver disease, liver fibrosis and ischemia/reperfusion injury (12)(13)(14)(15). Encouragingly, activation of HO-1 counteracts LPS-induced inflammatory and oxidative damage (16) and can also alleviate intestinal ischemia-reperfusion injury (17). Our previous study found that endogenous activation of HO-1 by cobalt protoporphyrin (CoPP) could suppress immune liver fibrosis (18), and another of our experiments showed that inhibiting HO-1 activity could be helpful in ameliorating BDL-induced liver cirrhosis (19).…”
Section: Introductionmentioning
confidence: 99%
“…Mice were killed at 24 hours after surgery. The dose/schedule selection for hemin and CrMP was based on literature.…”
Section: Methodsmentioning
confidence: 99%
“…13,48 In the present study, hemin was used in a dose of 30 mg kg -1 hemin ip as this dose was shown to counteract inflammation in different animal models. 22,25,38,45 As the time interval of administration of hemin before the inflammatory stimulus varied in these studies, we first investigated the HO-1 protein expression in intestinal muscular tissue at 6, 12, and 24 hours after administration of 30 mg kg -1 hemin ip in non-manipulated mice. This resulted in a time-dependent increase in HO-1 protein levels with the highest induction of HO-1 at 24 hours after administration of hemin.…”
Section: Investigation Of the Possible Role Of Nf-κb P65 In The Promentioning
confidence: 99%
“…Five randomly selected fields (×200) were captured from each slide using a light microscope in a blinded manner. The severity of intestinal injury was graded by two histopathologists who were initially blind to the experiment based on the criteria of Chiu's method [18,19].…”
Section: Evaluation Of Histological Injurymentioning
confidence: 99%